Phonological Processes Governing Borrowing from English to Lungu, Mambwe, and Namwanga Languages - Pethias Siame; Benjamin Amoakohene; Humphrey M. Kapau (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This article accounts for the phonological processes which govern borrowing from English to Lungu, Mambwe, and Namwanga (LuMaNa) languages. Guthrie (1948) classifies Lungu as M14, Mambwe as M15, and Namwanga as M22. Data were collected using elicitation, comparative, and document analysis methods. The paper employed Lexical Phonology and Morphology, and the comparative Bantu morphophonology theories. The study shows that LuMaNa languages use four major phonological processes to borrow from the English language, namely, epenthesis, sound substitution, metathesis or permutation, and vowel lengthening. Vowel epenthesis is used to create open syllables and break up consonant clusters during borrowing into LuMaNa. Consonant sound substitution is used to modify loanwords through devoicing. LuMaNa languages obey the following general devoicing rules; q/ð→t, q/ð→ f, z → s and defy the rest of the rules. Vowel sound substitution is achieved in LuMaNa through adaptation and nativisation of phonetic approximation. LuMaNa also borrow words through metathesis where two adjacent sounds reshuffle their positions to facilitate ease of articulation. Vowel length is used to borrow words from English to enable words to adjust and fit in the phonology of the target language. The study concludes that LuMaNa have similarities in the application of phonological processes during borrowing.